First record of the semi-slug Omalonyx unguis (d’Orbigny, 1837) (Gastropoda, Succineidae) in the Misiones Province, Argentina - Guzmán, Leila Belén (2018)
Fil: Guzmán, Leila Belén. Universidad Nacional de Misiones. Instituto de Biología Subtropical; Argentina.